PERBANDINGAN EKONOMI ISLAM DAN EKONOMI KAPITALIS - Moch Bukhori Muslim (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
The greatness of the capitalist economic theory has been questioned by many prominent economists. Due to the economic crisis occurred throughout history, it is necessary to bring out an alternative economic theory. Economic theory aspired is an economic system that is able to create justice and the welfare accompanied with blessing the world and the hereafter. Therefore, islamic economic theory can be considered as a way out to solve the contemporary economy problems. This article comparethe system of islamic economic and the capitalist economic takinginto account the philosophy, investment, distribution, theory of macro and micro aspects.DOI: 10.15408/aiq.v4i2.2551